2020
DOI: 10.3233/jad-200542
|View full text |Cite
|
Sign up to set email alerts
|

“Camminando e Leggendo ...   Ricordo” (Walking and Reading ...   I Remember): Prevention of Frailty Through the Promotion of Physical Activity and Reading in People with Mild Cognitive Impairment. Results from the TREDEM Registry

Abstract: Background: Frailty is a condition of increased vulnerability to exogenous and endogenous stressors, which is correlated with aging, functional decline, institutionalization, hospitalization, and mortality. Given the multifaceted nature of frailty, programs aimed at its prevention are recommended to act on multiple domains. Objective: The present intervention program aimed at assessing the effects of combined physical and cognitive training in older people with mild cognitive impairment (MCI) and at investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…It has been possible to verify some important advances in research on cognitive frailty in the scientific literature. Links between cognitive frailty and years of education continue to highlight the relationships between low wealth, low educational attainment and negative health events (Gallucci et al, 2020 ; Ruan et al, 2020 ; Wongtrakulruang et al, 2020 ), and the mediational role of active engagement in the relationship between cognitive frailty and falls (Zhao et al, 2020 ) appears as an emerging research topic. It is desirable that research on cognitive frailty progressively incorporates other relevant proxies of cognitive reserve, such as leisure activity and work complexity, as well as global measures of the cognitive reserve construct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been possible to verify some important advances in research on cognitive frailty in the scientific literature. Links between cognitive frailty and years of education continue to highlight the relationships between low wealth, low educational attainment and negative health events (Gallucci et al, 2020 ; Ruan et al, 2020 ; Wongtrakulruang et al, 2020 ), and the mediational role of active engagement in the relationship between cognitive frailty and falls (Zhao et al, 2020 ) appears as an emerging research topic. It is desirable that research on cognitive frailty progressively incorporates other relevant proxies of cognitive reserve, such as leisure activity and work complexity, as well as global measures of the cognitive reserve construct.…”
Section: Discussionmentioning
confidence: 99%
“…Ruan et al ( 2020 ) observed lower rates of physical and cognitive frailty in participants with an intermediate educational level (6–12 years) than in participants with a lower educational level. Similarly, Gallucci et al ( 2020 ) reported that education seems to be a protective factor in the incidence of frailty, with more years of education associated with robust or pre-frailty and low education associated with frailty. Wongtrakulruang et al ( 2020 ) associated low education level (primary school or less) a with higher risk of MCI and PF/pre-frailty.…”
Section: Relationship Between Cognitive Frailty and Cognitive Reservementioning
confidence: 90%
See 1 more Smart Citation
“…The other two articles [31,34] also had corresponding requirements for participants' age and physical condition. Other articles [38,40] identified research participants according to the pretest results of cognitive impairment scales at institutions, in communities, in apartments, and at other institutions that specialize in caring for older adults with cognitive impairment.…”
Section: Characteristics Of Previous Studiesmentioning
confidence: 99%
“…Targeted exercise programs have been shown to dramatically improve memory function and slow the rate of cognitive decline in people with MCI [22] . Furthermore, these therapies are successful in delaying and avoiding the onset of frailty [23,24] . With regard to MCI and Subjective Cognitive Decline (SCD), the 'Physical Activity Guideline for Older Australians' deals specifically with these conditions.…”
Section: Introductionmentioning
confidence: 99%